Model Penguasaan Tanah Pauman Di Kabupaten Karangasem - Suwitra, I Made; Widyantara, I Made Minggu; Sujana, I Nyoman (UI Scholars Hub, 2016)
In the period of kingdom, Pauman land was collectively owned by the community called pauman. After the independence and at the time Land Law had been imposed, even in some villages the land had been proposed to be owned individually and some of the land had been sold, so the problem discussed were; what model was applied for the pauman land ownership and how the management was done when the Land Law had been imposed. The model of the research was a research of normative law with legislation, concept, analytic, and case approach. The sources of the regulation which were used in this research were primary law sources, secondary law sources, and tertiary law sources which were collected by interview (affirmation), note taking and document. And then it was done interpretation technique. The result of the research showed that there was still collective ownership for pauman land in which the members of the owners were permanent and some were dynamic depended upon the development of the genealogical main owners. Meanwhile, in some villages the ownership tended to be secularly individualization through having the legality of the law in context of Land Law so that some pauman lands dismissed, infect the pauman land was the basic of the managing commitment and there was no more unity of community as the result of authority and ownership transference through trading them to other people. That’s why serious efforts are needed to preserve the pauman lands.